Efektivitas Hukuman Pidana dalam Menanggulangi Tindak Pidana Korupsi: Studi Perbandingan antara Indonesia dan China - Anak Agung Bagus Adhita Mahendra Putra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Corruption is an extraordinary crime with systemic impacts on a nation’s political, economic, and social stability. Various countries adopt different penal approaches to combat corruption, including Indonesia and China. This study aims to analyze and compare the effectiveness of criminal penalties in addressing corruption in both countries. The research uses a normative-juridical and comparative approach by examining legislation, empirical data, and relevant case studies. In Indonesia, the implementation of criminal sanctions tends to be more moderate, with imprisonment and fines being the dominant forms of punishment. However, enforcement faces challenges such as weak institutional independence and political interference. In contrast, China enforces much harsher penalties, including life imprisonment and the death penalty, as part of its